Medication Errors Among Hospitalized Adults in Medical Wards of Nekemte Specialized Hospital, West Ethiopia: A Prospective Observational Study - Gebre M (Dove Medical Press, 2021)
Mohammed Gebre,1 Nigatu Addisu,2 Ayantu Getahun,3 Jenber Workye,4 Busha Gamachu,5 Ginenus Fekadu,5 Tesfa Tekle,5 Bizuneh Wakuma,6 Getahun Fetensa,6 Balisa Mosisa,5 Getu Bayisa7 1Department of Pharmacology and Clinical Pharmacy, School of Pharmacy, College of Health Sciences, Addis Ababa University, Addis Ababa, Ethiopia; 2Department of Pharmacy, College of Health and Medical Sciences, Dilla University, Dilla, Ethiopia; 3Department of Public Health, Institute of Health Sciences, Wollega University, Nekemte, Ethiopia; 4Department of Pharmacy, College of Health Sciences, Debre Berhan University, Debre Berhan, Ethiopia; 5Department of Pharmacy, Institute of Health Sciences, Wollega University, Nekemte, Ethiopia; 6Department of Nursing, School of Nursing and Midwifery, Institute of Health Sciences, Wollega University, Nekemte, Ethiopia; 7Department of Pharmacy, College of Medicine and Health Sciences, Ambo University, Ambo, EthiopiaCorrespondence: Mohammed Gebre Email mohammed.gebre@aau.edu.etPurpose: A high prevalence of medication errors in older adults are due to a combination of different factors such as polypharmacy, polymorbidity, enrolment in several disease-management programs, and fragmentation of care that causes medication errors in all age groups. This study aims to assess the incidence and determinants of medication errors among hospitalized adults in medical wards of Nekemte Specialized Hospital (NSH), West Ethiopia.Patients and Methods: A prospective observational study design was conducted at Nekemte Specialized Hospital among hospitalized adults from October 30, 2018 to January 30, 2019. Data were collected by using checklist-guided observation and review of medication order sheets, medication administration records, and patient charts. To identify the independent predictors of medication errors, logistic regression analysis was used. Statistical significance was considered at a p-value < 0.05.Results: A total of 351 patients were included in the present study. The mean age of the patients was 40.67+15.78 years. A total of 813 medication errors were recorded. The most common stage for medication errors was physician ordering 263 (32.4%). In the multivariable analysis, age ≥ 65 years (AOR: 2.54, 95%CI: 1.12– 5.75, p=0.025), hospital stay ≥ 7 days (AOR: 2.16, 95%CI: 1.17– 3.98, p=0.014), number of medication taken (AOR: 1.75, 95%CI: 1.13– 2.73, p=0.013) and presence of comorbidity (AOR: 1.57, 95%CI: 1.01– 2.46, p=0.049) had shown statistical significance in predicting medication errors.Conclusion: Medication errors are common at Nekemte Specialized Hospital with an incidence of 48.3 per 100 orders, 231.6 per 100 admissions, and 433.4 per 1000 patient days. In particular, adults with older age, increased hospital stay, a greater number of medications, and presence of comorbidities were at greater risk for medication errors.Keywords: medication error, incidence, determinants, adults, Ethiopia